Safety evaluation of the food enzyme glucan‐1,4‐α‐maltohydrolase from the genetically modified Bacillus subtilis strain AR‐453 - EFSA Panel on Food Contact Materials, Enzymes and Processing Aids (CEP); Claude Lambré; José Manuel Barat Baviera; Claudia Bolognesi; Pier Sandro Cocconcelli; Riccardo Crebelli; David Michael Gott; Konrad Grob; Evgenia Lampi; Marcel Mengelers; Alicja Mortensen; Gilles Rivière; et al. (EFSA Journal)
Abstract The food enzyme glucan‐1,4‐α‐maltohydrolase (4‐α‐d‐glucan α‐maltohydrolase; EC 3.2.1.133) is produced with the genetically modified Bacillus subtilis strain AR‐453 by AB Enzymes GmbH. The genetic modifications do not give rise to safety concerns. The food enzyme is free from viable cells of the production organism and its DNA. It is intended to be used in baking processes. Dietary exposure was estimated to be up to 0.262 mg TOS/kg body weight per day in European populations. As the production strain of B. subtilis strain AR‐453 qualifies for the qualified presumption of safety (QPS) approach to safety assessment and no issue of concern arose from the production process, no toxicological data were required. A search for the similarity of the amino acid sequence of the food enzyme to known allergens was made and six matches were found. The Panel considered that, under the intended conditions of use, the risk of allergic reactions by dietary exposure cannot be excluded, but the likelihood is low. Based on the data provided, the Panel concluded that this food enzyme does not give rise to safety concerns under the intended conditions of use.